Role of Artificial Intelligence and Smart Grids in Energy Companies in the European Union Member States - Ioanid , Alexandra; Palade, Dan (European Journal of Sustainable Development, 2023)
Artificial intelligence has started to play a crucial part in many industries throughout the world starting in 2023. One of the sectors that stands to gain the most out of the implementation of AI-driven solutions is the power sector, especially during a time of major transitions. The purpose of this qualitative study is to identify the level at which well-established companies from the power sector are when it comes to integrating AI into their daily operations. The focus of the research is on the Romanian power sector, mainly on companies that have the largest potential for implementing AI solutions (production, transport/distribution, and suppliers and traders). To do so, the author first performs secondary research into the definition and utilization of artificial intelligence at a global level and then, conducts primary research into the state of AI deployment in the Romanian power sector. The data was collected in the summer of 2023 by conducting interviews with industry experts with an average experience of more than 30 years in the industry. The originality of the article comes from the fact that there are no academic papers meant to assess the current level of deployment of AI solutions in the Romanian power sector, and there is little literature that presents a condensed view of AI applications at a local level. The results of the study point out an early interest in implementing AI solutions. The limitations and further research paths are also presented. Keywords: artificial intelligence, smart grids, strategy, renewable energy sources, clean energy, new technologies, decentralized power system